Pengaruh Efektivitas Kredit Usaha Rakyat (KUR) Terhadap Peningkatan Profit Usaha Mikro (Studi Kasus Pada Nasabah Bank Rakyat Indonesia Kantor Cabang Tulang Bawang) - Budiman, Anton; Arif Hidayat, Miftahul; Sri Putri, Novia (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research is motivated by problems in the MSME sector in terms of capital, and considering how important MSME is to the national economy. The government program in increasing MSME financing access to financial institutions with a guarantee pattern is the People's Business Credit (KUR). This study aims to determine the effect of the effectiveness of People's Business Credit (KUR) on increasing micro business profits on customers of Bank Rakyat Indonesia, Tulang Bawang Branch Office. Assessment of effectiveness in this study uses four aspects, namely the accuracy of the use of funds, the amount of credit, credit load, and procedures based on customer assessment. The type of research used is causal associative research with a quantitative approach. The population of this study were BRI customers at the Tulang Bawang Branch Office who used the People's Business Credit (KUR) program, totaling 644 people. Samples were taken by 64 people with purposive sampling method. Data collection techniques using a questionnaire. Data analysis technique using multiple regression. The results of this study indicate the Effectiveness of People's Business Credit (KUR) from the aspect of Accuracy in the Use of Funds, Amount of Credit, and Procedures in the effective category, while from the Accuracy of Credit Expenses aspect it is in the very effective category. The effectiveness of KUR seen from the four aspects has a positive and significant effect on increasing micro business profits.